Results of Surgical Treatment (Modified Sugiura-Futagawa Operation) of Portal Hypertension Associated to Complete Splenomesoportal Thrombosis and Cirrhosis - Mercado, Miguel Angel (Hindawi Publishing Corporation, 1999)
Background Hemorrhagic portal hypertension, secondary to both intrahepatic and extrahepatic portal hypertension, is an uncommon entity. In this condition, the extrahepatic and the intrahepatic obstruction of the portal vein, due to chronic liver disease, produce a more severe form of hemorrhagic portal hypertension that is more difficult to control. The results of surgical treatment (modified Sugiura- Futagawa operation) in this subset of patients is analyzed. Methods Among 714 patients with a history of hemorrhagic portal hypertension, 14 cases were found with histologically proven liver cirrhosis and complete splenomesoportal thrombosis demonstrated by means of preoperative angiography. Patients with incomplete (partial) splenomesoportal thrombosis were excluded. There were nine males and 5 females with a mean age of 51 years. Alcoholic cirrhosis was demonstrated in 50% of the cases, post hepatitic cirrhosis in 28%, primary biliary cirrhosis in 7%, and cryptogenic cirrhosis in 14%. There were nine Child-Pugh A and 5 B cases. All cases were treated by means of our modified Sugiura-Futagawa procedure. Results Bleeding recurrence from esophagogastric varices was shown in one case, colonic varices in one case and hypertensive gastropathy in another of the survivors. Post operative encephalopathy was shown in 3 of the cases. The thirty-six month survival rate was 30% (Kaplan-Meier). Conclusions The combination of intrahepatic plus extrahepatic portal hypertension has a worse prognosis. Treatment options are limited (sclerotherapy and/or devascularization), because shunt surgery, TIPS and liver transplantation have a very restricted role and postoperative outcome is poor.